Um modelo integrado de promoção do sucesso escolar (MIPSE): a voz dos alunos - Cabral, Ilídia (2017)
This paper focus on the characterization and analysis of an integrated model of school success promotion (MIPSE) based on team teaching in its first year of implementation. The study presented is based on part of the monitoring process consisting of the application of a questionnaire to the students involved in the project, as well as of a focus group. The analysis and interpretation of the collected data make it possible to conclude that the MIPSE is perceived by the generality of students as an attractive and motivating pedagogic model, able to generate more and better learning. However, some opportunities for improvement are to be mentioned, such as the improvement of the pedagogic value of some of the activities to be done by the best students; the use of more diverse and active teaching and learning strategies, able to imply every student in school work and the necessity of abandoning a logic of remediating the learning difficulties of some of the students and engage in a logic that aims to promote better learning opportunities for everyone.